H3K27-altered diffuse midline glioma of the adult thoracic spinal cord: A case report with literature review and clinical insights - Halit A. Alioglu; Mert Yavuz; Omar Alomari; Mikail Devrus Adem Ceylan; Zuhal Kus Silav; Mustafa Güdük (Surgical Neurology International, 2026)
Background: Primary spinal cord gliomas are rare, with adult-onset diffuse midline glioma (DMG), H3K27-altered, representing an even smaller and highly aggressive subset. Recently classified as a World Health Organization (WHO) Grade 4 entity, these tumors typically arise in midline structures and carry a poor prognosis regardless of histological appearance. While more common in children, adult cases are increasingly recognized, though spinal involvement remains poorly characterized, often mimicking other intramedullary or extramedullary pathologies. Case Description: A 46-year-old morbidly obese male presented with a 3-month history of progressive paraparesis. Neurological examination revealed severe lower extremity weakness (2/5–0/5), hyperreflexia, and bilateral clonus. Magnetic resonance imaging showed a diffusely infiltrative, contrast-enhancing intramedullary lesion extending from T5 to T10. Diagnostic and surgical planning were significantly hindered by technical limitations related to the patient’s obesity and claustrophobia. On the 10 th day of admission, acute neurological deterioration prompted an emergency T5–T10 laminectomy and intramedullary biopsy. Intraoperatively, the spinal cord was markedly edematous and infiltrative. Postoperatively, the patient’s condition worsened with new-onset upper extremity weakness. Repeat imaging eventually revealed cranial progression of the tumor into the cervical spinal cord. Despite intensive supportive care, the patient developed respiratory failure and deceased. Histopathological and immunohistochemical analysis confirmed the diagnosis of DMG, H3K27-altered (WHO Grade 4), characterized by H3K27M nuclear positivity and loss of H3K27me3. Conclusion: This case highlights the aggressive biological behavior and rapid clinical progression of adult spinal H3K27-altered DMG. It underscores the profound diagnostic and surgical challenges posed by patient-specific factors such as morbid obesity, which can delay critical imaging and intervention. Given the dismal prognosis and tendency for rapid rostral extension, early molecular diagnosis and multidisciplinary management are vital, though treatment remains largely palliative in advanced spinal cases.